Survey of the Information-Seeking Behaviour of Hospital Professionals at a Public Cancer Hospital in Greece Proves the Value of Hospital Libraries - DeRosa, Antonio (Evidence Based Library and Information Practice, 2013)
Objective – To study the information-seeking practices of hospital staff and weigh the impact of hospital libraries on effective information-seeking. Design – Survey questionnaire. Setting – Large public cancer hospital in Greece. Subjects – The authors surveyed 49 physicians, 43 nursing staff members, 25 administrative staff members, 23 paramedical staff members, and 5 technical staff members, totaling 145 health professionals. Methods – Participants were given a questionnaire comprised of five parts: general information (including gender, age, education, position, and professional experience); questions on computer and Internet accessibility; questions regarding individual information needs; questions on information-seeking obstacles; and a question regarding the satisfaction with the current degree of information availability in the hospital. The last question was ranked using a 5-point Likert scale. Each questionnaire was distributed with a cover letter explaining the anonymity and consent of the respondent. Hospital members were randomly selected using a number generator and respondents returned completed surveys to the hospital personnel office in a sealed envelope within a specified time frame. The sampled group was representative of the overall population of the hospital. Main Results – The authors discuss demographic data of respondents: 65.7% were women; 56.7% were over 40 years old; 29.0% were graduates of higher technological institutes; 28.3% were university graduates; 9.7% held a postgraduate degree; 8.3% had a PhD; and 1.4% had only secondary education. As for the remainder of the survey questions: 64% of respondents had access to the Internet both at home and at work, while only 8.2% had no access to the Internet at all; most respondents noted using the Internet for seeking scientific information (83.0%) and e-mail communication (65.3%); the main obstacle respondents noted experiencing when seeking information was the lack of time (3.7 score on Likert scale). A lack of information services was second to the time issue with a Likert scale score of 3.6. Conclusion – Based on the research results, the authors affirmed the invaluable role of hospital libraries. The hospital library can help to eliminate the obstacles faced by healthcare professionals by providing support in the areas of weakness based on the survey results. This can be made possible through the hospital library’s involvement in educational activities, investigation of information technologies, and development of information services to accommodate the difficulties regularly experienced by hospital staff. Researchers revealed that funding for hospital libraries in Greece is an issue preventing many new initiatives, that there is no association to represent hospital libraries in Greece, that the few libraries operating in hospitals in Greece are understaffed with no administrative control, and the majority of Greek hospitals do not have adequate library facilities. These drawbacks contribute to the information-seeking challenges experienced by Greek healthcare professionals.